The Relationship of Academic Anxiety with Self Efficacy - Nia Febbiyani Fitri; Firman Firman (Universitas Negeri Padang, 2020)
The fact found today is that there are still many students who experience a decrease in self efficacy. Self efficacy is a student's belief about his ability to overcome various situations that arise in his life in the form of difficulty in the task, strength in beliefs and behavior. One factor that is thought to influence this is academic anxiety. Academic anxiety can result in low confidence in students. This can be seen when students cannot reach the target in the near future, students feel anxious about the symptoms of experiencing panic and headaches, and sometimes students tend to give up because they are not sure of their abilities. This research aims to reveal a picture of the relationship of academic anxiety with self the efficacy of Padang 1 high school students. This research is a descriptive correlational study, with a sample of 272 students obtained using simple random sampling techniques. Data collection instruments used a scale questionnaire that was compiled by itself in data collection using the Google forms application. The results of this study indicate that academic anxiety of SMA Negeri 1 Padang students is in the moderate category, and in terms of self-efficacy it is also in the moderate category.